Confinement of neutral fermions by a pseudoscalar double-step potential in 1+1 dimensions - de Castro, A. S.; Pereira, W. G. (Elsevier B.V., 2003)
The problem of confinement of neutral fermions in two-dimensional space-time is approached with a pseudoscalar double-step potential in the Dirac equation. Bound-state solutions are obtained when the coupling is of sufficient intensity. The confinement is made plausible by arguments based on effective mass and anomalous magnetic interaction. (C) 2003 Elsevier B.V. B.V. All rights reserved.